Pelatihan Kompetensi Guru dalam Kolaborasi Sebagai Wujud Pembelajaran Berdiferensiasi bagi Anak Berkebutuhan Khusus di Sekolah Inklusif - Sinta Yuni Susilawati; Ediyanto; Wiwik Dwi Hastuti; Muchamad Irvan; Nanda Viorella; Riyanda Putri Earlyarini (Politeknik Piksi Ganesha Indonesia, 2025)
This community service activity is motivated by the findings of a problem at the State University of Malang Laboratory Kindergarten, namely the need for a better understanding of the responsibilities of regular teachers towards students with special needs in the classroom, as well as the lack of collaboration in implementing differentiated learning. Therefore, this service program aims to improve teachers' ability to collaborate for differentiated learning in inclusive schools at the preschool level. The methods used include material delivery and activity evaluation. This program targets teachers and principals. The results showed that teachers gained a very good understanding of collaboration in differentiated learning. Based on the pre-test and post-test results, there was a significant improvement with a score of 65.85% (moderately effective category).